COMPARISON OF HSP90 EXPRESSION IN CONJUNCTIVAL INTRAEPITHELIAL NEOPLASIA AND CONJUNCTIVAL SQUAMOUS CELL CARCINOMA: Oral Presentation - Experimental Study - Ophthalmologist - TRISSA WULANDA PUTRI; IBRAHIM (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Heat shock protein 90 (HSP90) participates in stabilizing and activating client proteins involved in malignant transformation. This study aims to determine whether there are different values for the expression of HSP90 in Conjunctival Intraepithelial Neoplasia (CIN) and Conjunctival Squamous Cell Carcinoma (CSCC). Methods : A total of 24 OSSN samples, including 15 cases of CIN and 9 cases of CSCC were evaluated. The immunohistochemical expression of HSP90 was assessed using a scoring system based on the percentage of positive staining of nuclear and cytoplasmic cells, then the intensity of staining was evaluated using the German Immunoreactive Score. Results : In the study, the average cytoplasmic Immunoreactive Score in CIN was 9.87 and CSCC was 16.89 with a significant result (p=0.007), while the average nuclear Immunoreactive Score in CIN was 11.30 and CSCC was 14.50 with insignificant results (p=0.274). The results of the correlation test showed that the cytoplasmic expression groups with low categories were all in CIN as much as 6 (100%) so they had a ratio of 6:0. and the high category of HSP90 cytoplasmic expression group was only found in CSCC as many as 2 (100%) samples with a ratio of 0:2. The results of the correlation test using the Pearson test obtained a significant correlation value (p=0.006) with a moderate correlation strength (r=0.545). Conclusion : There are differences in the expression of cytoplasmic and nuclear HSP90 but only the cytoplasmic expression of HSP90 is significantly associated with CIN and CSCC.